Utilization Strategy of East Java Provincial Government Assets - Nurbaiti Isnaini (Journal of Economics, Business, and Government Challenges, 2019)
The implementation of regional autonomy provides an opportunity for the East Java government to increase regional autonomy by exploring all the potential resources available in order to increase East Java PAD. The increase of new sources of income is always categorized as an effort to increase local taxes and retributions, but it should be opened up a new potential that is still buried so far, in the form of assets owned by the East Java provincial government which has not been developed as an asset that can increase revenue for the regional treasury of East Java Province. To achieve these objectives, it is necessary to analyze the causes and constraints of not optimal utilization of assets owned by the East Java provincial government, which are normatively the basis of the implementation of the utilization of the aforementioned laws and regulations. The results of this study propose changes to accelerate the process of optimizing the utilization of assets owned by the East Java provincial government.